2020
DOI: 10.1371/journal.pone.0236034
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patterns of multimorbidity in the Jamaican population: A comparative analysis of latent variable models

Abstract: Background Evidence suggests that the single-disease paradigm does not accurately reflect the individual experience, with increasing prevalence of chronic disease multimorbidity, and subtle yet important differences in types of co-occurring diseases. Knowledge of multimorbidity patterns can aid clarification of individual-level burden and needs, to inform prevention and treatment strategies. This study aimed to estimate the prevalence of multimorbidity in Jamaica, identify population subgroups with similar and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 44 publications
1
15
0
1
Order By: Relevance
“…LCA results have been previously described [ 16 ]. To summarize, indices and probability plots collectively supported the four-class model as the optimal baseline model, based on identification (i.e., the model converged on the same solution the majority of the time), entropy (i.e., distinctiveness of the latent classes) and meaningful interpretation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…LCA results have been previously described [ 16 ]. To summarize, indices and probability plots collectively supported the four-class model as the optimal baseline model, based on identification (i.e., the model converged on the same solution the majority of the time), entropy (i.e., distinctiveness of the latent classes) and meaningful interpretation.…”
Section: Resultsmentioning
confidence: 99%
“…This is the first study to examine the social patterning of multimorbidity in Jamaica. Building on identified latent classes [ 16 ], this study shows that beyond differences in the type and number of diseases comprising multimorbidity patterns, there are also important social differences associated with class membership. Specifically, the study found that advancing age and recent health service use were significantly associated with all multimorbidity patterns.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations